SOFTWARE DEVELOPMENT AND COMPARATIVE STUDY OF THERMAL CONDUCTIVITY MODELS FOR REFRIGERANTS - Rahmannida Machendra, Alifia
The models and database of the transport property of refrigerants, which includes thermal conductivity and viscosity, has been a topic of interest amongst researchers to optimize the process of engineering analysis and design, which results in the development of various mathematical models. As of today, Indonesia has not yet developed an engineering software that holds the database for the thermal conductivity of refrigerants that allows the user to easily compare between different existing models. A study of existing models is required to find the most accurate model for applications in thermo fluids. To solve this problem, a program is developed that calculates the thermal conductivity of 26 different refrigerants. The development of this software is done by programming with C++ language with the help of WxWidget in order to create the Graphical User Interface (GUI) and become a desktop-based application. The software includes mathematical models, which includes Garagheizi’s model, Heyen’s equation of state, and DIPPR 9G model. The comparative study analyses the result of computation of the three models. With a maximum average BIAS value of 0.11%, average AAD value of 0.35%, and average STD value of 0.24%, generally, the DIPPR model is the most recommended to be used.